1990
DOI: 10.1021/ac00209a023
|View full text |Cite
|
Sign up to set email alerts
|

Microemulsion structure and its effect on electrochemical reactions

Abstract: Changes in the microstructure of oil-in-water microemulsions were identified electrochemically by using ferrocene derivatives, methyl viologen, and ferricyanide as the electroactive probes. Microdroplets as well as the bicontinuous microstructure were detected. This was accomplished by determining diffusion coefficients of the probes. Use of probes of different hydrophobicity/hydrophilicity and charge made it possible to investigate different microenvironments of microemulsions including oil, water, and surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 29 publications
5
53
0
Order By: Relevance
“…The oxidation potential of Fc in the ME is therefore more anodic than in acetonitrile (E o '= 0.415 V vs. standard calomel electrode, SCE) and in water (E o '= 0.163 V vs. SCE). 24 On the other hand, as expected, the voltammogram in the cathodic region is not altered by the presence of Fc.…”
Section: Electrochemical Measurementssupporting
confidence: 72%
See 2 more Smart Citations
“…The oxidation potential of Fc in the ME is therefore more anodic than in acetonitrile (E o '= 0.415 V vs. standard calomel electrode, SCE) and in water (E o '= 0.163 V vs. SCE). 24 On the other hand, as expected, the voltammogram in the cathodic region is not altered by the presence of Fc.…”
Section: Electrochemical Measurementssupporting
confidence: 72%
“…The oxidation potential of Fc in the ME is therefore more anodic than in acetonitrile (E o '= 0.415 V vs. standard calomel electrode, SCE) and in water (E o '= 0.163 V vs. SCE). 24 On the other hand, as expected, the voltammogram in the cathodic region is not altered by the presence of Fc.By comparing the diffusion coefficient values for Fc oxidation from the oil phase and for water from droplets in the ME, it is observed that D Fc is, respectively, 60 and 40 times higher than D w/o for ME containing, respectively, isoamyl and amyl alcohol. Considering that water droplets are surrounded by a film of nonpolar tails of dodecyl sulfate anions and amyl or isoamyl chains, 14 its diffusion through the continuous oil medium must be slower than the one for Fc molecules.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…Furthermore, a bicontinuous microstructure, such as a network of water tubes in an oil matrix, or a network of oil tubes in a water matrix, with hydrocarbon and water regions stretching over large distances, has been identified in the intermediate regions. [20,21] Conductivity is frequently used to investigate structure and structural changes in microemulsions; estimating a microstructure using conductivity measurements is based on percolation theory. The static percolation model, which attributes percolation to the appearance of a bicontinuous water structure, has been proposed to describe the mechanism of percolation in traditional microemulsions.…”
Section: Microregions Of the Il Microemulsionmentioning
confidence: 99%
“…[1][2][3] However, the application of these techniques in nanoheterogeneous systems, including microemulsions (MEs), has been scarcely exploited. MEs are optically transparent, isotropic and thermodynamically stable systems.…”
Section: Introductionmentioning
confidence: 99%